2018
DOI: 10.3390/educsci8040187
|View full text |Cite
|
Sign up to set email alerts
|

Education for Sustainable Development through International Collaboration. A Case Study on Concepts and Conceptual Change of School‐Students from India and Austria on Gender Equality and Sustainable Growth

Abstract: Dealing with the great challenges of the 21st century requires far reaching changes in the lifestyle and perceptions of humans to ensure an appropriate quality of life for all, now and in the future. To provide people with the necessary competencies, the UN initiated the Education for Sustainable Development (ESD) program. The two-year research-education, cooperative project ‘AustrIndia-4QOL’ aims to contribute to the goals of ESD. It is based on a collaboration between students from schools in Austria and Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…Specifically, the intervention positively affected their awareness about gender equality, and increased positive attitudes and socio-emotional capacities, by improving their understanding of their own identities, agency, better managing their emotions, as well as increasing their self-confidence, communication, and decision-making and negotiation skills. These findings are in line with recent evidence highlighting the importance of students' self-reflection on their own and others' behaviors, which in turn could lead to alternatives to deal with sensitive issues as gender equality and its challenges [32]. In line with the determinants of behavior (change) identified in the Theory of Planned Behavior [24], the results indicate that the lessons of the program encouraged students' self-explorations of positive or negative evaluations of gender and gender equality (attitudes), and their beliefs regarding gender behaviors, as well as perceptions of important others' opinions and behaviors in this respect (i.e., social norms).…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, the intervention positively affected their awareness about gender equality, and increased positive attitudes and socio-emotional capacities, by improving their understanding of their own identities, agency, better managing their emotions, as well as increasing their self-confidence, communication, and decision-making and negotiation skills. These findings are in line with recent evidence highlighting the importance of students' self-reflection on their own and others' behaviors, which in turn could lead to alternatives to deal with sensitive issues as gender equality and its challenges [32]. In line with the determinants of behavior (change) identified in the Theory of Planned Behavior [24], the results indicate that the lessons of the program encouraged students' self-explorations of positive or negative evaluations of gender and gender equality (attitudes), and their beliefs regarding gender behaviors, as well as perceptions of important others' opinions and behaviors in this respect (i.e., social norms).…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, research hypothesis 2.2 can neither be simply verified nor can it be rejected. From statements the students wrote at the beginning and at the end of the face-to-face collaboration, it can be concluded that the Indian students increased their claims for more economic growth of the countries of the Global South [70]. It can be assumed that the direct contrast with the living-standards of one of the wealthiest countries worldwide may have prevented an increased willingness to act towards more sustainable lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…For all ten Indian students and their accompanying teacher, it was their first journey outside India. Once in Austria, the Indian students were hosted by the families of their project partners, which not only lowered costs but also enabled the Indian students a direct insight into the lifestyles of their counterparts [70].…”
Section: Study Samplementioning
confidence: 99%
“…Tonbuloglu et al [14] argues that a holistic process involving educational institutions does not accept students' separation and fully supports social and cultural diversity. Developing a multicultural perspective and encouraging people to think requires cognitive education that enhances caring for others [15]. In the context of this significant transformation, it is crucial to develop a curriculum and tactical plan to be used in education, and educators, students themselves, and their families also have an essential role to play [16].…”
Section: Introductionmentioning
confidence: 99%